Evaluasi Speech Therapy Dalam Mengoptimalkan Kemampuan Bahasa Ekspresif Pada Anak Speech Delay - Ratu Nur Aisyah Sri Winarti; Shafa Fitriyani; Anisa Rizqi Rahmatillah; Lathipah Hasanah (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2022)
Children who experience speech delay, especially in their expressive language skills will have difficulty in pronunciation. Therefore, speech therapy is needed in helping the problems faced by children. The purpose of this study was to analyze the stages of speech therapy at Kitty Center Green Garden, speech therapy activities in optimizing expressive language skills, identification of supporting and inhibiting factors of speech therapy and speech delay in children's language skills after attending speech therapy. This type of research uses a descriptive qualitative approach. Data analysis used the CIPP (Context, Input, Process, Product) evaluation model. Data collection techniques in this study were observation, interviews, and documentation. The results of this study indicate: 1) Context Evaluation, showing a good category with the results of the study being able to provide good services. 2) Input Evaluation, showing a good category with research results, namely the facilities and infrastructure provided are adequate in speech therapy activities. 3) Process Evaluation, showing a good category with research results, namely therapy services according to the development of the client. 4) Product Evaluation, showing a good category with the results of the research, namely the speech therapy services provided can produce changes in speech therapy recipients.